2008
DOI: 10.1007/s11629-008-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant species diversity along an altitudinal gradient of Bhabha Valley in western Himalaya

Abstract: The present study highlights the rich species diversity of higher plants in the Bhabha Valley of western Himalaya in India. The analysis of species diversity revealed that a total of 313 species of higher plants inhabit the valley with a characteristic of moist alpine shrub vegetation. The herbaceous life forms dominate and increase with increasing altitude. The major representations are from the families Asteraceae, Rosaceae, Lamiaceae and Poaceae, suggesting thereby the alpine meadow nature of the study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 25 publications
11
70
1
Order By: Relevance
“…Gottfried et al (2012) reported ample evidences that ongoing climate change continuously affects the Himalayan Vegetation along with its different components. Rapid geo-climatic variations at different altitudes in Himalaya generate diverse vegetation structure and high species diversity (Chawla et al 2008). Intensity of major threats to forest ecosystems and biodiversity along altitudinal gradient is directly measured by compositional changes in forest structure.…”
Section: Introductionmentioning
confidence: 99%
“…Gottfried et al (2012) reported ample evidences that ongoing climate change continuously affects the Himalayan Vegetation along with its different components. Rapid geo-climatic variations at different altitudes in Himalaya generate diverse vegetation structure and high species diversity (Chawla et al 2008). Intensity of major threats to forest ecosystems and biodiversity along altitudinal gradient is directly measured by compositional changes in forest structure.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of richness along the elevational gradient. We found a not very pronounced humpshaped pattern in the overall species distribution along the elevational gradient (Figure 2), which is a pattern found in different groups of vascular plants along tropical elevational gradients, such as ferns (Salazar et al 2015), terrestrial herbs (Willinghöfer et al 2012) and shrubs (Chawla et al 2008). Rahbek (1995) suggested that the distribution of plants in tropical areas is affected by the high variation of environmental factors that can change substantially in small regions, and this causes differences in the form of distributional patterns.…”
Section: Discussionmentioning
confidence: 56%
“…total number of species actually present and the degree to which they are important, is useful in comparing communities (Simpson 1949;Pielou 1969;Peet 1974). Many researchers (Palmer 1992;Huston and DeAngelis 1994;Lieberman et al 1996;Lomolino 2001;Chawla et al 2008) have contended that change in altitude results in difference in species composition, but in the present study species composition of plant communities at different elevations exhibited minor differences (Table 2). This may be due to long biotic range and wide environmental tolerance of constituent species (Goodall 1979).…”
Section: Discussionmentioning
confidence: 69%
“…The diversity of the tree layer can influence herb layer diversity by modifying resource availability and environmental conditions relevant to herb layer plants (Chawla et al 2008;Jacob et al 2009;Wulf and Naaf 2009;Vockenhuber et al 2011;Bhat 2012). While linkages between the diversity of the herb and tree layer have been commonly reported (Gilliam 2007), most studies so far compared herb layer diversity between forest types in other parts of Himalaya (Adhikari et al 1992;Bahera 2007;Chawla 2008;Kukshal et al 2009;Kharkwal and Rawat 2010;Khan et al 2012). Little is known on how the diversity of the tree layer affects herb layer diversity across an environment gradient in Himachal Pradesh in Northwest Himalaya though some results do report relationship between tree and herb layer diversity (Bhat 2012).…”
Section: Introductionmentioning
confidence: 99%